The Role of Nanoparticle Elasticity on Biological Hydrogel Penetration - Chathuri I. Sodimanage; Marc Schneider (Pharmaceutics)
The latest advancements in nanomedicine have led to increased therapeutic efficacy and reduced complications. However, nanoparticle penetration is significantly influenced by biological hydrogels, such as mucus, the extracellular matrix, biofilms, and nucleoporins. Solely modifying well-studied physicochemical properties like size, charge, and surface chemistry is insufficient to fully elucidate or overcome these barriers. Recent studies have investigated the impact of particle elasticity, a relatively unexplored yet crucial physicochemical property influencing many biological processes. Hence, it is important to explore the impact of particle elasticity on penetrating biological hydrogels. This review examines biological hydrogels’ structural and functional features as diffusion barriers, provides an overview of particle elasticity, key elasticity measurement techniques, and explores strategies for elasticity modulation in nanoparticles, such as composition, crosslinking density, and structural design. Furthermore, nanoparticle penetration mechanisms, influenced by particle deformability, hydrogel mesh size, and adhesive interactions, are investigated by integrating theoretical and experimental findings. The evaluation of experimental data reveals the commonly observed particle elasticity trends in mucus penetration, extracellular matrix permeation, and corneal penetration of nanoparticles. Overall, this review offers valuable insights into designing next-generation nanomedicines capable of overcoming biological barriers.